Quantum Floquet spectra of surface and bulk state of topological insulator - Kumar, Upendra; Kumar, Vipin; Kushwaha, Ajay Kumar; Cho, Sung Beom (Physica E: Low-Dimensional Systems and Nanostructures, 2023)
Topological insulators are a new class of material, which consists of insulating bulk and conducting surface state. In this study, we investigated the behavior of bulk and surface state of topological insulator under a high frequency electromagnetic field, produce a kind of oscillation called as Floquet oscillation. We successfully identified the classical and quantum behavior of Floquet oscillation in the prospective of collapse revival spectra. This work shows the bulk and surface states behavior of a topological insulator with the help of Floquet and Rabi frequency and describes the dominancy of Floquet oscillation in the low energy physics. Numerical simulation has been applied for verifying the Floquet approximation.
Keywords: Bloch-Siegert shift; Bulk state; Bulk surfaces; Collapse revival spectrum; Floquet; Floquet spectrum; Floquet theory; Rabi frequency; Spectra's; Topological insulators; Bloch–Siegert shift; Collapse revival spectra; Floquet theory; Rabi frequency; Topological insulators